Kebijakan Pencegahan Dan Penanganan Kekerasan Seksual di Lingkungan Perguruan Tinggi - Handayani, Triana Dianita (Jurnal Pembangunan Hukum Indonesia, 2025)
Criminal law enforcement is based on the principle of "equality before the law", however in practice criminal law enforcement against sexual violence in higher education environments has its own procedures, which influence the length of the criminal law enforcement process. This research aims to examine criminal law enforcement procedures for sexual violence in higher education environments. The research method used is normative juridical. The results of the research show that the policy for handling and preventing sexual violence in higher education, which is regulated in Minister of Education and Culture Regulation No. 46 of 2023 specifically stipulates that reports of alleged sexual violence in higher education can be submitted to the Violence Prevention and Handling Team (TPPK), Task Force, government regions in accordance with their authority and/or the Ministry. So the existence of these provisions has made it difficult to enforce criminal law against sexual violence in higher education.